Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan - Ria Estiana; Nurul Giswi Karomah; Yoshia Agustin Saimima (POLITEKNIK LP3I JAKARTA, 2023)
This study aims to determine the effect of work environment and work discipline on employee performance of PT Horiguchi Engineering Indonesia. The research method used is a quantitative survey method with descriptive and associative research types. This study uses primary data, by distributing questionnaires to employees of PT Horiguchi Engineering Indonesia as respondents. The sampling technique used in this research is the sampling technique using the probability sampling method, namely the simple random sampling technique with a total sample of 46 respondents. The dependent variable is employee performance at PT Horiguchi Engineering Indonesia, while the independent variable is the work environment and employee work discipline. Based on the F test, the results of this study indicate that the work environment and work discipline have a positive effect on the performance of PT Horiguchi Engineering Indonesia's employeesKey words: Work Environment, Work Discipline, Employee Performavance